Development of an Information System for Monitoring, Data Collection and Reporting of Turtle Conservation in the Essential Ecosystem Area (KEE) of Kili Kili Beach, Trenggalek Regency, Based on the Website - Muhammad Derry Ramadhan; Vian Dedi Pratama (Journal of Social Research, 2025)
As a maritime country, Indonesia has abundant marine biodiversity, encompassing sea turtles, whose dwindling numbers have serious ecosystem effects. Conservation work is done in various locales, including Pantai Taman Kili-kili, Trenggalek, where the Community Monitoring Group (Pokmaswas) has set up conservation measures. But conservation is hard work, especially doing it well enough so numbers don't keep declining. There's limited human resources and that means conservation in real time works better if done with smart tools. The Pokmaswas needs a system for making recording and reporting almost instantaneous so that any trouble making a dive at the beach is reported posthaste. In developing this system, researchers using the waterfall approach, resulting in a web-based application built using the Next.js framework with an atomic design system. To evaluate system acceptance, Blackbox testing was conducted with 17 test points, achieving a 100% success rate. Whitebox testing included 16 test points, also yielding a 100% success rate. For user acceptance testing, two aspects were assessed: functional and non-functional testing. The functional testing consisted of 14 test points, with a 97.6% success rate. The non-functional testing get 91,7% score